Development of Web-Based Mathematics Learning to Improve the Mathematical Power - Beni Setiawan; Nurapni Sopia; Andri Andri (Department of Mathematics Education University of Muhammadiyah Malang, 2022)
This study aims to develop a mathematics learning web to improve the mathematical power of junior high school students through valid, practical, and effective development. This study uses development research methods with the ADDIE development model. The model steps are analysis, design, development, implementation, and evaluation. The research subjects were 30 Class VIII students on SMP Negeri 2 Sintang and SMP Swasta Nusantara Indah Sintang. In this study, product trials consist of expert validation, small-scale trials, and student questionnaires. The analysis technique measures student’s mathematical power using the gain score calculation. The results of the study show (1) a mathematics learning web developed to increase valid mathematical power for junior high school students. (2) the mathematics learning web meets the practical criteria in its use from good student responses, and (3) there is an increase in student’s mathematical power with moderate criteria after learning on the mathematics learning web.